Effects of Ambient pH on the Growth and Development, Pathogenicity, and Diacetoxyscirpenol Accumulation of Muskmelon Fruit Caused by Fusarium sulphureum - Qili Liu; Lan Yang; Huali Xue; Yang Bi; Qianqian Zhang; Yuanyuan Zong; Xiao Li (Journal of Fungi)
Ambient pH, an important environmental factor, affects the growth, pathogenicity, and mycotoxin production of pathogenic fungus. Fusarium sulphureum is one of the predominant causal agents causing fusarium rot of muskmelon. In this study, we investigated the effects of ambient pH on fusarium rot development and diacetoxyscirpenol (DAS) accumulation in muskmelon infected with F. sulphureum, then analyzed the possible mechanisms in vitro and in vivo. The results suggested that ambient pH 6 was more conducive to the growth, pathogenicity, and mycotoxin production of F. sulphureum in vitro. Ambient pH 6 was also more favorable for secretion of cell wall-degrading enzymes for the pathogen to degrade the cell wall of the host plant and up-regulated the relative expression of genes involved in DAS biosynthesis, thus aggravating fruit disease and DAS accumulation. However, when the pH of the inoculated spore suspension was too acidic or too alkaline, the opposite results were observed.